EUTHANASIA AS AN APPLIED PROBLEM OF THE MODERN ETHICS - Кошетар, У. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Тhe essential features, philosophical and world-view aspects of euthanasia as an applied problem of the modern ethics are analyzed in the article.